Explanation and Social Theory - Holmwood, John. author. aut Link
X, 244 p.
Keywords: The book ranges widely over modern social theory, giving detailed treatments of major sources to identify common themes and deficiencies in apparently disparate schools of thought. The object is to lay bare negative assumptions forming methodologies in modern social theory in order to redirect the social sciences towards real problems and the progressive consequences of their solution. Examples are given and, throughout, the continuity of particular and general concerns is demonstrated.